In-situ estimate of coating by equivalent circuit for PEO of AZ31B. (2nd January 2023) - Wang, S.; Liu, Y. C.; Liu, H. M.; Lan, Y. F.
ABSTRACT: The paper discusses an in-situ estimated methodology of coating using the equivalent circuit for the plasma electrolytic oxidation (PEO) process. An equivalent circuit of the second-order nonlinear structure can be proposed from the transient load waveform and the arc image recorded during pulsed bipolar PEO treatment. The transfer function of the linear part of the model was derived from Kirchhoff's law and Laplace's transformation rule; the nonlinear part of the model was fitted using Fitting Theory. Then the calculation method of each element value was derived in the equivalent circuit. The characterisation results of the coating properties show that the changes of different element values by the equivalent circuit can reflect the changes in coating thickness, coating density and discharge intensity. The relationship between the values of several elements and the microstructure of the coating is analysed comprehensively; a prediction method for the corrosion resistance of the coating is provided.